- #1

- 120

- 0

its pretty much just integrating now

y(x) = e^(x) (int[e^(-x)*-sin(2x)dx] + c)

ans => y(x)= 1/5(sin2x-2cos2x)+c

thanks in advance

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Quadruple Bypass
- Start date

- #1

- 120

- 0

its pretty much just integrating now

y(x) = e^(x) (int[e^(-x)*-sin(2x)dx] + c)

ans => y(x)= 1/5(sin2x-2cos2x)+c

thanks in advance

- #2

berkeman

Mentor

- 59,689

- 9,847

- #3

- 1,235

- 1

If [tex] y(x) = e^{x}\int e^{-x}\times -\sin 2x \; dx [/tex]

- #4

- 120

- 0

ya thats what i dont understand..

- #5

- 1,235

- 1

use integration by parts.

- #6

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 964

Share: